(untitled) (Research, Society and Development, 2020)
This study took the relationship of self-confidence and body image to students at FKIP UMN Alwashliyah. In this case, self-confidence and body image as independent variables and personal fable as dependent variables. Adolescence is one of the stages in human life which is a period of transition from childhood to adulthood. At this stage adolescents will experience changes both physically, cognitively and psychosocial. In line with physical changes, young women tend to develop a high level of concern for their physical changes. The way adolescents perceive their physical condition will affect the level of their personal ability. With high trust and a positive body image will increase the personal level of the teenager. The objectives of this study were to determine: (i) the relationship between self-confidence and body image with personal fable in UMN AW students; (ii) The relationship between self-confidence and personal ability in UMN AW students; (iii) The relationship between body image and personal fable in UMN AW students. The research method used in this research is quantitative method with a sample of 2 classes from semester 2, each class totaling 30 people. Thus the data taken is in the form of a questionnaire, using Pearson Correlation analysis. Data analysis was performed using SPSS 23 for windows.